Mechanisms of power, victimization and autonomy in the health care system - Takács, Erzsébet (METSZETEK Társadalomtudományi Folyóirat, 2022)
The aim of this paper is to describe power relations, doctor-patient relationships among themany ongoing changes in health care from sociological point of view. This paper is based oninterviews with 17 people who work in various fields of health care. To conduct the interviews aswell as to write the paper, a number of concepts and theoretical approaches were resorted to:Dominique Memmi’s ’delegated biopower’, Eve Bureau and Judith Hermann-Mesfen’s notion of’contemporary patient’, François Dubet’s concept of institutional programme as well as results ofHungarian health sociology. The main focuses of interest of the paper are role models in healthcare, the characteristics and consequences of new doctor-patient relations, their manifestationsin Hungary as well as potentials of defencelessness and autonomy in Hungarian health care.